Systematic density functional theory study of the structural and electronic properties of constrained and fully relaxed (0 0 1) surfaces of alumina and hematite. Issue 5 (13th April 2017) - Corum, Katie W.; Huang, Xu; Bennett, J. W.; Mason, S. E.
Abstract: Owing to their widespread use in a variety of technological applications, as well as their prevalence as naturally occurring phases in the environment, there is a prolific amount of computational research devoted to the surfaces of metal oxides. However, there is no standard approach for how to best represent the surface structurally in quantum mechanical modeling, specifically in the standard supercell slab geometry that is amenable to density functional theory calculations that employ periodic boundary conditions. There is a choice in both slab thickness and in how the atomic positions are treated during geometry optimisations; the atomic coordinates can either be fully relaxed or partially fixed. Constraining the atomic positions of select layers of the slab can decrease overall computational cost and is often reported to have a minimal effect on the details of the optimised geometries. In this study, we compare fully relaxed structures of alumina ( ) and hematite ( ) (0 0 1) surfaces to two slab models in which either one or two stoichiometric layers, denoted as trilayers, are constrained to bulk positions. We go on to study the electronic structure of the slab models, and we also assess how modeled reactivity is affected through studies of atomic chemisorption on the slab models. Our results suggest that while structural differences between partially constrained or fully relaxed slab models may be subtle, both the electronic structure and modeled reactivity can vary significantly in quantitative and qualitative ways.